Frecuencia de lesiones del esqueleto apendicular en pacientes caninos atendidos en el área de radiología de la Clínica de Animales Menores de la Universidad Nacional Mayor de San Marcos (Lima, 2012-2016) - Rojas G., Saúl (2022)
The frequency of lesions of the appendicular skeleton diagnosed in canines was evaluated in the radiology area of Small Animal Clinic of the Faculty of Veterinary Medicine of the Universidad Nacional Mayor de San Marcos during the period 2012-2016. In total, 2552 radiological recordings made in the appendicular skeleton were analyzed. Of these, 43.3% (n=1106) presented traumatic injuries, 23.2% (n=591) orthopedic injuries, 12.7% (n=323) degenerative injuries, 2.7% (n=69) injuries compatible with osteomyelitis, 1.7% (n=42) lesions compatible with neoplasms, and 0.5% (n=13) lesions compatible with hypertrophic osteodystrophy. Among trauma injuries, the bone structures with the highest frequency of fracture were the pelvis (35.1%; n=388) and femur (26.9%; n=298) and among orthopedic injuries were patellar luxation (36.9%; n=218) and hip dysplasia (36.6%; n=216). Traumatological injuries were more frequent in juvenile canines (46.5%), and orthopedic injuries in mature adults (42.2%). Males had a higher frequency of trauma (58.3%) and orthopedic (61.2%) injuries compared to females. Trauma injuries were more common in undefined crossbreds (60.3%), and orthopedic injuries in purebred canines (70.0%).